A randomized multicenter trial to compare functional outcome and complications of surgical procedures for low rectal cancers - STRATILATOVAS, Eugenijus; SANGAILA, Egidijus; SINKEVIČIUS, Žalvyras; BURNECKIS, Arvydas; POŠKUS, Eligijus; STRUPAS, Kęstutis (Acta medica Lituanica, 2011)
Background. The outcomes after different low rectal resection types applied for rectal cancer treatment are still uncertain. The aim of the investigation was to evaluate long-term functional results, the rate of complications and post-operative lethality after rectum low resection operations (connection with J-pouch group: coloplasty – group 2 and “straight” anastomosis – group 3).Patients and methods. In 2003, a randomized study was started and completed on December 2007. The study included 82 patients (38 females and 44 males). The patients were randomized into three groups. They were suffering from cancer stage I–III.Results. There were no postoperative deaths after 82 resections with total mesorectal excision (TME) and low connection. The overall rate of postoperative complications was 28%, and the rate of anastomosis suture leakage was 11%. The rate of postoperative complications was 20.7% (6 patients) in group 1, 28.6% (6 patients) in group 2, 34.3% (11 patients) in group 3. The rate of complications was substantially higher in groups 2 and 3; however, this difference was statistically not significant (p = 0.2636). The functional results after 3, 6, 9, 12 and 24 months showed no statistical difference among the groups; moreover functional results after 24 months in all groups were similar (p = 0.046). Anastomosis with or without pouch does not influence postoperative lethality. The incidence of complications and suture leakage is higher in cases of straight anastomosis; however, this finding is not statistically significant. Necrosis was observed only in patients for whom anastomosis with pouches were performed.Conclusion. Comparison of functional results after 3, 6, 9, 12 and 24 months showed no statistically significant differences among the groups.The necrosis of pulled-down bowel was observed only in the pouch groups.Keywords: rectal cancer, anastomosis, J-pouch, coloplasty, functional results